Wealth, rights, and resilience: An agenda for governance reform in small-scale fisheries - Ratner, Blake D.; Allison, Edward H. (Wiley, 2012)
The diversity of social, ecological and economic characteristics of small‐scale fisheries in developing countries means that context‐specific assessments are required to understand and address shortcomings in their governance. This article contrasts three perspectives on governance reform focused alternately on wealth, rights and resilience, and argues that – far from being incompatible – these perspectives serve as useful counterweights to one another, and together can serve to guide policy responses. In order to better appreciate the diversity in governance contexts for small‐scale fisheries it puts forward a simple analytical framework focused on stakeholder representation, distribution of power, and accountability, and then outlines principles for identifying and deliberating reform options among local stakeholders.